Role of Interventional Radiologists in the Management of Lower Extremity Venous Insufficiency - Hardman, Rulon L.; Rochon, Paul J. (Seminars in Interventional Radiology, 2013)
Lower extremity venous insufficiency affects over half of all women. Interventional radiologists should be aware of the clinical evaluation of women with venous insufficiency and classification of disease. Endovascular therapies available for treatment of lower extremity venous insufficiency include: endovenous laser ablation, radiofrequency endovascular ablation, and sclerotherapy. The interventional radiologist should be versed on which therapy to select in each clinical presentation and the procedural techniques. The authors review the role of the interventional radiologist in managing this lower extremity venous disorder.
Keywords: chronic venous insufficiency; varicose veins; endovascular laser ablation; endovascular radiofrequency ablation; sclerotherapy; interventional radiology